Determinants on Whistleblowing Intention: an Insight from Indonesian - Lili Wahyuni; Anis Chariri; Etna Nur Afni Yuyetta (International Journal of Supply Chain Management, 2021)
This study aimed to analyze the influence of determinants of whistleblowing attitudes toward whistleblowing behavior, perceived ethical climate and locus of control on whistleblowing intention. The population in this study was 111 employees of the Pratama Tax Office in Semarang City. The census method was used in collecting data and samples of 91 respondents. Data were processed using Warp PLS 5.0. The results showed that the attitude towards behavior had a positive effect on whistleblowing intentions, the perceived ethical climate had a positive effect on whistleblowing intentions and locus of control had a positive effect on whistleblowing intentions.